An in-vivo microfluidic assay reveals cardiac toxicity of heavy metals and the protective effect of metal responsive transcription factor (MTF-1) in Drosophila model. - Zabihihesari, A.; Parand, S.; Coulthard, A.B.; Molnar, A.; Hilliker, A.J.; Rezai, P. (3 Biotech, 2022)
Previous toxicity assessments of heavy metals on Drosophila are limited to investigating the survival, development rate, and climbing behaviour by oral administration while cardiac toxicity of these elements have not been investigated. We utilized a microfluidic device to inject known dosages of zinc (Zn) or cadmium (Cd) into the larvae's hemolymph to expose their heart directly and study their heart rate and arrhythmicity. The effect of heart-specific overexpression of metal responsive transcription factor (MTF-1) on different heartbeat parameters and survival of Drosophila larvae was investigated. The heart rate of wild-type larvae decreased by 24.8% or increased by 11.9%, 15 min after injection of 40 nL of 100 mM Zn or 10 mM Cd solution, respectively. The arrhythmicity index of wild-type larvae increased by 58.2% or 76.8%, after injection of Zn or Cd, respectively. MTF-1 heart overexpression ameliorated these effects completely. Moreover, it increased larvae's survival to pupal and adulthood stages and prolonged the longevity of flies injected with Zn and Cd. Our microfluidic-based cardiac toxicity assay illustrated that heart is an acute target of heavy metals toxicity, and MTF-1 overexpression in this tissue can ameliorate cardiac toxicity of Zn and Cd. The method can be used for cardiotoxicity assays with other pollutants in the future.